UTILIZING TOOTH DOLL MEDIUM TO IMPROVE SELF-DEVELOPMENT CAPABILITY âIN BRUSHING TEETHâ OF MENTALLY DISABLEDFIRST GRADERS - Tiyas, Lina Rahayuning; ., Sudarsini (Department of Special Education, 2016)
The aim of this research is to describe of (1) the utilization of tooth doll medium to improve self-development of mentally disabled students, and (2) the improvement of studentsâ self-development capability by using tooth doll medium for mentally disabled. This research uses classroom action research (CAR). The result showed that (1) the utilization of tooth doll medium make students play an active role in learning. (2) the utilization of tooth doll medium enabled to improve the first gradersâ self-development capability.Â Tujuan penelitian ini adalah untuk mendiskripsikan (1) pemanfaatan media boneka gigi untuk meningkatkan bina diri siswa tunagrahita, dan (2) peningkatan kemampuan praktik bina diri dengan menggunakan media boneka gigi untuk siswa tunagrahita. Penelitian ini mnenggunakan pendekatan penelitian tindakan kelas. Hasil penelitian ini menunjukkan (1) pemanfaatan media boneka gigi membuat siswa berperan aktif dalam pembelajaran, (2) pemanfaatan media boneka gigi dapat meningkatkan kemampuan praktik bina diri siswa tunagrahita kelas I.